Pengaruh Konsentrasi Gula dan Waktu Fermentasi terhadap Aktivitas Aantioksidan Minuman Seduh Kombucha Daun Belimbing Wuluh (Averrhoa bilimbi Linn.) - Vania Aristawidya; Annis Catur Adi (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
The consumption of sugar-sweetened beverages (SSBs) in Indonesia continues to increase and is associated with the risk of obesity, diabetes, and cardiovascular diseases due to oxidative stress. Kombucha has potential as a functional antioxidant beverage; however, its use is still dominated by Camellia sinensis, limiting the utilization of local ingredients. Bilimbi leaves (Averrhoa bilimbi Linn.) have high antioxidant activity and potential as an alternative substrate. This study aimed to analyze the effect of fermentation time variations (4, 7, and 14 days) and sugar concentrations (10% and 15%) on the acceptability and antioxidant activity of bilimbi leaf kombucha, as well as to determine the best formulation. The study used a true experimental design with a Completely Randomized Design (CRD) involving six formulations (F1–F6) and one control (F0). Antioxidant activity was analyzed using the DPPH method. The results showed that fermentation time and sugar concentration significantly affected antioxidant activity.). The highest antioxidant activity was found in F2 (IC50 98.67 ppm, strong category). F2 was determined as the best formulation due to its antioxidant activity. F2 has the potential to be developed as an alternative functional beverage to reduce SSB consumption. Further research is recommended to conduct stability testing and in vivo studies.